Limitations of Serological Diagnosis of Typical Cat Scratch Disease and Recommendations for the Diagnostic Procedure - Myrto Koutantou; Konstantinos Kambas; Sofia Makka; Pierre-Edouard Fournier; Didier Raoult; Emmanouil Angelakis (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Cat scratch disease (CSD) is the most common cause of bacterial infectious lymphadenopathy, especially in children, but its diagnosis still remains challenging. Serological assays are widely applied due to their simplicity and the non-invasive sampling. However, these techniques present several limitations, including not well-defined antigen preparation, assay conditions and cutoff titers, severe cross-reactions with other species and organisms, and the notably ranging seroprevalence in the normal population. The objective of this study is to review the literature in order to determine the best diagnostic procedure for the diagnosis of CSD. Methods. Databases including PubMed, Medline, Google Scholar, and Google were searched to determine the best diagnostic procedure for the diagnosis of CSD. A total of 437 papers were identified and screened, and after exclusion of papers that did not fulfill the including criteria, 63 papers were used. Results. It was revealed that sensitivities of serological assays varied from 10% to 100%. Indeed, more than half of the studies reported a sensitivity lower than 70%, while 71% of them had a sensitivity lower than 80%. Moreover, specificities of serological assays ranged from 15% to 100%, with 25 assays reporting a specificity lower than 90%. Conclusion. It is considered that molecular assays should be the gold standard technique for CSD confirmation, and physicians are reinforced to proceed to lymph node biopsy in suspicious CSD cases.